Music Therapy as a Tool for Alleviating Anxiety and Pain in Patients Undergoing Gastrointestinal Endoscopy - Wei Long; Zhu Yang; Shengju Lu; Huiping Luo; Fang Jiang (Noise and Health, 2025)
Abstract Objective The purpose of this study was to explore how music therapy impacts anxiety and pain levels in patients undergoing gastrointestinal endoscopy. Methods This was a retrospective study conducted from July 2021 to July 2024. A total of 367 patients who underwent gastrointestinal endoscopy at our hospital were selected as subjects. After excluding 67 cases, 300 patients were finally included. Based on whether they received music therapy or not, patients were divided into a music therapy group (n = 165) and a routine nursing group (n = 135). The music therapy included listening to music with headphones while waiting for and undergoing endoscopy. Before and 5 minutes after the endoscopy, the anxiety status [State-Trait Anxiety Inventory (STAI)], pain level [Numerical Rating Scale (NRS)], and hemodynamic characteristics were compared between the two groups. Results Before the endoscopy, there were no significant differences in STAI scores, NRS scores, and hemodynamic characteristics between the two groups (P > 0.05). After the endoscopy, the State Anxiety Inventory score of the STAI (37.88 ± 8.12) and the NRS score (3.95 ± 0.95) in the music therapy group were significantly lower than the STAI score (40.85 ± 8.38) and NRS score (4.55 ± 1.03) in the routine nursing group, with t-values of 3.106 and 5.239, respectively (P < 0.05). No significant differences in hemodynamic characteristics—pulse oxygen saturation, heart rate, and mean arterial pressure—existed between the two groups after the endoscopy (P > 0.05). Conclusion This study showed that music therapy effectively reduced anxiety and pain in patients undergoing gastrointestinal endoscopy, highlighting its significant clinical value.